Future research directions for climate-sensitive social protection - Desai, Bina; Läderach, Peter; Meddings, George; Campbell, Raramai (2025)
The limited global coverage of social protection, fragmented adaptation efforts, and a volatile political and security situation in the Sahel mean that the ambitions of existing social protection approaches may miss the mark. Better understanding the barriers to scaling up and the avenues towards prudently adapting existing programs would be a first step in designing impactful national systems. This article builds on a global review and a regional study in the Sahel on the potential alignment of climate adaptation and social development finance in low-income communities. The hypothesis is that rather than radically redesigning programs to make them respond to a broad range of climate risks, enhancing existing mechanisms by integrating climate risk information in program design may yield better results. However, a lack of in-depth studies of national and regional experience means that valuable lessons are not captured. Recent, promising investments in Mauritania and the wider Sahel region in developing and maintaining nationally owned social registries, and in making provisions for fragile contexts and displaced populations, are not sufficiently documented. This gap opens up a research agenda on the role of adaptive social protection in climate action in sub-Saharan Africa and beyond.